57. Cerebellar direct current stimulation does not interfere with motor cortex excitability and transcallosal communication in humans. Issue 4 (April 2016) - Tocco, P.; Casula, E.P.; Rocchi, L.; Chieffo, R.; Monaco, S.; Bertolasi, L.; Hannah, R.; Rothwell, J.C.
Abstract : The cerebellum is involved in motor execution. It controls the primary motor cortex (M1) activity and ensures the correct amount of inhibition to produce the right motor output. Besides, it plays an important role in the error monitoring mechanisms during bimanual coordination. We investigated the role of the cerebellum in the modulation of M1excitability and M1-M1 interhemispheric inhibition (IHI) using transcranial direct current stimulation (tDCS). Thirteen healthy volunteers received cerebellar tDCS at 2 mA for 20 min among three randomized sessions (anodal right, anodal left, sham). M1 excitability (PA direction, single-pulse, 1 mV MEP) and short-latency IHI (PA direction, paired-pulse, conditioning stimulus 110% RMT, ISI 8 and 10 ms) were determined before, 5 min after the onset, and 30 min after the end of stimulation. All measures were taken bilaterally. The M1 excitability compared before, during and after cerebellar tDCS did not change among sessions (ANOVA, p  > 0.05). The short-latency M1-M1 IHI was always determined, but it did not change among sessions (ANOVA, p  > 0.05). The cerebellar anodal tDCS does not interfere with the motor cortex excitability and with the transcallosal inhibition at rest.